Ensino de ciências em Cabinda/Angola: condições da prática docente, idéias de professores e desafios - BUZA, Juliana Lando Canga (Universidade Federal do Pará, 2012)
This study presents a qualitative research developed with Science teachers of an Elementary School in the Province of Cabinda, Angola. The school where the twelve teachers involved in the research work trains them to perform in all the grades of basic education. The research, held in the narrative approach, is divided into seven sections. The teaching practice conditions and teachers’ ideas and challenges were some of the issues taken into consideration. In order to achieve my goals, I try to rescue the historical context of the country, considering the five centuries of settlement until Independence, in 1975; as well as the three decades of Civil War up to the peaceful moments shared by the people nowadays. After that, I make a brief view of Education history focusing on the changes made during these four periods: Colonial, Post-Colonial, Civil War and the peaceful moments. The analysis was carried out based on a questionnaire of sixteen open questions applied to all the twelve teachers. The teachers’ answers were organized into four categories: motivation for teaching and affinity for the profession; what the teachers demonstrated to know about Science and the teaching of such subject; the teaching working conditions and the teachers’ continuing education; the self-vision of their teaching practices and of their teaching of Science. These categories led to the analysis of the data in relation to the teaching of Science in Cabinda, which resulted in the following: the majority of the teachers who work with elementary education do not have graduate formation for such; they had been motivated by some other reasons for teaching; their performance, as Science teachers, occurs by their sole and own effort; the working conditions are very poor - there’s lack of bibliographical material and difficulties to access information; there are no Biology, Physics and Chemistry graduate courses to qualify teachers for high-school education; there are not continuing educational programs for Science teachers. Even so, the teachers face the challenging task to teach to the youth, they also feel proud of being teachers in Cabinda and demonstrate optimism and hopefulness to continue their studies, at a higher educational level.